Ecojustice education : toward diverse, democratic, and sustainable communities - Martusewicz, Rebecca A.; Edmundson, Jeff.; Lupinacci, John. (New York : Routledge, 2011)
'Designed for introductory social foundations or multicultural education courses, this text offers a model for cultural ecological analysis and a pedagogy of responsibility, providing teachers and teacher educators with the information and classroom practices they need to help develop citizens who are prepared to support and achieve diverse, democratic, and sustainable societies in an increasingly globalized world.'--back cover.
Includes bibliographical references (p. [316]-330) and index.
Keywords: Social ecology -- Study and teaching; Environmental education; Environmental ethics; Sustainability; Education -- Social aspects